Encapsulated Co–Ni alloy boosts high-temperature CO2 electroreduction - Wenchao Ma; Jordi Morales-Vidal; Jiaming Tian; Meng-Ting Liu; Seongmin Jin; Wenhao Ren; Julian Taubmann; Christodoulos Chatzichristodoulou; Jeremy Luterbacher; Hao Ming Chen; Núria López; Xile Hu (Nature, 2025)
Abstract Electrochemical CO2 reduction into chemicals and fuels holds great promise for renewable energy storage and carbon recycling1–3. Although high-temperature CO2 electroreduction in solid oxide electrolysis cells is industrially relevant, current catalysts have modest energy efficiency and a limited lifetime at high current densities, generally below 70% and 200 h, respectively, at 1 A cm− 2 and temperatures of 800 °C or higher4–8. Here we develop an encapsulated Co–Ni alloy catalyst using Sm2O3-doped CeO2 that exhibits an energy efficiency of 90% and a lifetime of more than 2,000 h at 1 A cm− 2 for high-temperature CO2-to-CO conversion at 800 °C. Its selectivity towards CO is about 100%, and its single-pass yield reaches 90%. We show that the efficacy of our catalyst arises from its unique encapsulated structure and optimized alloy composition, which simultaneously enable enhanced CO2 adsorption, moderate CO adsorption and suppressed metal agglomeration. This work provides an efficient strategy for the design of catalysts for high-temperature reactions that overcomes the typical trade-off between activity and stability and has potential industrial applications.